REFORMS IN THE FIELD OF LAND RELATIONS REGULATION IN UZBEKISTAN - Abdunazarov Oybek Abdumutalibovich (Web of Journals Publishing, 2025)
This article examines the ongoing agricultural and land reforms in the Republic of Uzbekistan, with a focus on land privatization and efficient land use as critical components of sustainable economic development. The paper highlights the unique characteristics of land as a natural and economic resource, the legal and institutional reforms aimed at improving land management, and the implications of privatization for economic activity, investment attraction, and property rights protection. Special attention is given to the implementation of land privatization laws, urbanization strategies, and pilot programs such as the Syrdarya region experiment. The analysis emphasizes the importance of transparent, market-oriented land governance for fostering agricultural productivity, supporting entrepreneurship, and building a prosperous society.
Keywords: Uzbekistan, land reform, land privatization, agricultural policy, land ownership, property rights, urbanization, agricultural land, land legislation, sustainable development.